New possibilities of the active damping of vibrations - Bajkowski, Jerzy; Tadzik, Piotr; Zalewski, Robert (Wydawnictwa AGH, 2007)
In presented paper a new proposition of granular structure, composed on the basis of granular materials placed in hermetic space with underpressure, as a damping material for vibrated steel beam has been described. Three different types of laboratory tests have been described: fundamental strength properties of granular testing specimen, bending of granular beam and damping of the steel beam vibrations using special granular structures. Obtained results revealed that the behavior of such a structure could be easily controlled by underpressure parameter. Also damping characteristics of vibrated steel beam could be controlled by changing internal underpressure value.

W artykule zaprezentowano zastosowanie struktury, zbudowanej na bazie luźnego granulatu umieszczonego w szczelnej przestrzeni z podciśnieniem, do tłumienia drgań belki stalowej. Omówiono trzy typy badań eksperymentalnych: podstawowe badania wytrzymałościowe próbki struktury granulowanej, badania zginania belek granulowanych oraz badania tłumienia drgań belki stalowej za pomocą wspomnianych materiałów. Wyniki przeprowadzonych eksperymentów jednoznacznie potwierdzają możliwość wpływania na parametry fizyczne granulowanych konglomeratów za pomocą parametru podciśnienia i tym samym na postacie charakterystyk tłumienia drgań swobodnych belki stalowej.
Nowe możliwości aktywnego tłumienia drgań
Mechanics
References. s. 159.
Keywords: granular materials; laboratory tests; underpressure; beam vibrations; materiały granulowane; badania eksperymentalne; podciśnienie; drgania belki